The Uses of AI And Technology in Media and Material Development of Merdeka Belajar - Melati, Sela Eka; Aini, Nurul; Wahyuni, Anisya Fatul (Proceeding International Conference on Education, 2023)
The advancement of AI and Technology has increased in numerous fields of our lives, and the education field has dealt with it. On the other hand, our national curriculum for education, called Kurikulum Merdeka, has flexibility in terms of learning, sources, and developing the material for the teaching and learning process. Along with the advancement of educational material in curriculum merdeka, numerous kinds of sources are utilized, like books, e-learning tools, media of teaching, and so on. There was also an effect of AI and Technology as platforms for learning sources, particularly English as one of the languages taught within the Indonesian Education field. The objective of this research is to determine the significance of AI and technology in the development of Merdeka Belajar learning resources for teachers. Furthermore, the purpose of this research is to investigate AI and technology which may be used as a variety of learning methods and material development utilizing a Merdeka Belajar curriculum, to make learning in class more enjoyable. This research employs library research as an approach to determining which AI technologies are employed in the advancement of English resources based on the Merdeka Belajar curriculum. Data is collected from previous studies on related subjects. Based on the findings of this study, we can identify the use of AI and technology to build English learning media and materials based on the Merdeka Belajar Learning Guidelines.